Hubungan Kualitas Tidur Dengan Kualitas Hidup Pada Lansia Di Surakarta - Nur Chasanah; Supratman Supratman (Jurnal Berita Ilmu Keperawatan, 2018)
When human get an older, there more likely to experience physical, mental, spiritual, economic and social problems. One of the most basic problems in the elderly is the health problems caused by the degenerative process. The process of degeneration in the elderly causes an effective sleep time decreases, and causes not achieving adequate sleep quality and cause the sharing of sleep complaints that can disrupt the quality of life of the elderly This study aims to determine the relationship quality of sleep with quality of life in elderly in Surakarta. This research is descriptive correlative research with cross sectional approach. The study population was 334 elderly people in Surakarta. The sample of 96 elderly was obtained by proportional random sampling technique. Data collection used the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the WHOQL-BREF (World Health Organization of Life-BREF) questionnaire, while the data analysis used Chi Square test. Chi Square test results p-value of 0.002 so that Hypothetis null was rejected. The conclusion of the study where the level of quality of elderly sleep mostly good, the quality of life of the elderly mostly less and there where correlation level of quality of sleep with quality of life of elderly in Surakarta where better quality of sleep quality of life of elderly higher.